2016
DOI: 10.3168/jds.2016-11002
|View full text |Cite
|
Sign up to set email alerts
|

Activities of amylase, proteinase, and lipase enzymes from Lactococcus chungangensis and its application in dairy products

Abstract: Several enzymes are involved in the process of converting milk to lactic acid and coagulated milk to curd and, therefore, are important in dairy fermented products. Amylase, proteinase, and lipase are enzymes that play an important role in degrading milk into monomeric molecules such as oligosaccharides, amino acids, and fatty acids, which are the main molecules responsible for flavors in cheese. In the current study, we determined the amylase, proteinase, and lipase activities of Lactococcus chungangensis CAU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 41 publications
(51 reference statements)
0
25
0
1
Order By: Relevance
“…The qualitative evaluation of lipase activity of all strains was determined on MRS agar plates prepared with 10% tributyrin (Yuanye Biotechnology Co., Ltd.), and the formation of a transparent halo on the plate indicated that the microorganisms metabolized the lipids. Lipase activity was measured by potentiometric titration with an indicator (Konkit and Kim, 2016).…”
Section: Screening Labs In Kazak Cheese With Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative evaluation of lipase activity of all strains was determined on MRS agar plates prepared with 10% tributyrin (Yuanye Biotechnology Co., Ltd.), and the formation of a transparent halo on the plate indicated that the microorganisms metabolized the lipids. Lipase activity was measured by potentiometric titration with an indicator (Konkit and Kim, 2016).…”
Section: Screening Labs In Kazak Cheese With Enzyme Activitymentioning
confidence: 99%
“…Lactic acid bacteria can be used as a starter culture for cheese fermentation because of their ability to release proteases, lipases, or β-galactosidases to form a unique taste, aroma, and texture (Juan et al, 2016). During cheese fermentation, the most important features and functions of LABs are (1) the conversion of lactose in milk into small molecular monosaccharides, galactose, and glucose, which promote the formation of cheese flavor (Blaya et al, 2018); (2) the degradation of proteins into peptides and free amino acids (FAAs) in cheese; and (3) the decomposition of lipids into fatty acids (Konkit and Kim, 2016). Proteases are key enzymes in the hydrolysis of protein during cheese fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable samples collected were a good source of presumptive LAB isolates with important enzymatic activities, which can influence a food product with enhanced flavor, texture, or nutritional features. Additionally, these enzymatic properties can be used in the production of substances with industrial importance, such as lactic acid and diacetyl [ 18 , 38 ] or for the production of enzymes to be used at an industrial scale, such as amylase [ 17 , 18 ]. The LAB isolates selected bases on their enzymatic activity were also identified by molecular techniques.…”
Section: Discussionmentioning
confidence: 99%
“…LAB can also be a source of novel strains with enzymatic activities of interest for food production or other industrial use of enzymes [ 16 , 17 ]. Enzymes of microbial origin are more desirable than enzymes from other sources as they may show enhanced catalytic activities, present higher yields, and economic culture media can be used in microbial growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation